Review of Graphene Properties in View of its Use as a Substrate for Matrix-Free Mass Spectrometry - Gabovich, V.A.; Pokrovskiy, V.A. (Хімія, фізика та технологія поверхні, 2010)
Short review of the graphene basic properties is given. This material is discussed, in particular, as a possible ionization support for mass spectrometry. The attention is paid to the possible role of intrinsic and deliberately induced structural defects in electronic and chemical properties of graphene substrates. Представлено короткий огляд основних властивостей графену. Цей матеріал розглядається з точки зору можливого використання як підкладки для мас-спектрометричних досліджень. Також розглянуто вплив природних та штучно створених дефектів на електронні та хімічні властивості графенових структур. Представлен краткий обзор основных свойств графена. Этот материал рассматривается с точки зрения возможного использования в качестве подложки при масс-спектрометрических исследованиях. Также рассмотрена роль естественных и искусственно созданных дефектов в электронных и химических свойствах графеновых структур.